Perbandingan Sistem Hukum Indonesia dan India terhadap Tindak Pidana Pemerkosaan dalam Perkawinan (Marital Rape) Berdasarkan CEDAW - Andi Wulan Rahmadania (CV Rewang Rencang, 2025)
This study aims to determine the comparison of the Indonesian and Indian legal systems regarding the crime of rape in marriage. The formulation of the problem in this study is how the legal unity in Indonesia and India regarding the crime of rape in marriage (marital rape). And how the differences or comparisons of the Indonesian and Indian legal systems regarding the crime of rape in marriage. The findings of this study indicate that in the context of comparative law regarding marital rape in Indonesia and India, the approach of these two theories can be seen from how both countries handle the issue without explicit recognition of marital rape as a crime. In Indonesia, marital rape is not specifically regulated in the Criminal Code and is only recognized in the context of domestic violence if there is an element of coercion, as stated in the Domestic Violence Act. In India, marital rape is also not recognized in the Indian Penal Code (IPC), unless the victim is under 18 years old.